Pengaruh Proses Rekrutmen, Seleksi, Dan Gaji Terhadap Kinerja Karyawan Pada Bank Rakyat Indonesia Syariah Cabang Palembang - Olini Gusma Yanti; Hilda Hilda; Zuul Fitriani Umari (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
The background of this study aims to determine the effect of the recruitment process (x1), selection (x2) and salary (x3) on the performance of employee (y) at BRI Syariah Bank Palembang branch. To find out how much influence the independent variables (recruitment process, selection, and salary) have on the dependent variable (employee performance) multiple linear regression analysis is used. Respondents in this study were employees of Bank BRI Syariah, Palembang branch. Sampling using saturated sampling technique as many as 40 respondents. The data collection method used in this research is distributing questionnaires to employees online using a link. The analytical tool in this study used SPSS version 21.0. Using research instrument test data analysis method, classical assumption test, multiple linear regression analysis and coefficient of determination (R2) test. Based on the results of the recruitment variable t test the value of t count > t table (2,793 > 2.02809) is obtained and a significance value of 0,008 < 0,05 means Ho is rejected and Ha is accepted.On the selection variable, the value of tcount > t table (2,237 > 2.02809) Is obtained and a significance value of 0,032 < 0,05 means that Ho is rejected and Ha is accepted, and the results of the salary variable t test obtained tcount > t table (3,728 > 2.02809) and a significance value of 0,001 < 0,05 means that Ho is rejected and Ha is accepted. Based on the value of the the f test results, the value of f count > f table is (13,099 > 2,87) with a sig value (0,000 < 0,05 ). Thus the hypothesis is accepted, this means that there is a positive and significant effect simultaneously between the variables of recruitment, selection and salary on the performance of employees at the Palembang branch of BRI Syaraih bank.